AI-Driven Business Analytics: Its Impact on Strategic Decision-Making (An Empirical Study on Educational Institutions in the Kingdom of Saudi Arabia) - Oraif , Ghada (Journal of Ecohumanism, 2024)
This study explores the impact of AI-driven business analytics on strategic decision-making within educational institutions, specifically in the Kingdom of Saudi Arabia. The research examines how these technologies enhance decision-making efficiency and assesses the factors that influence their integration, such as technical infrastructure, organisational culture, and employee training. The study aims to identify the challenges that hinder the successful implementation of AI technologies in strategic frameworks. An inductive and deductive approach was adopted, with a questionnaire as the primary data collection tool. The study targeted decision-makers in educational institutions across the Kingdom of Saudi Arabia to gather insights into their experiences with AI-driven business analytics. The results reveal a high level of interest in integrating AI technologies, with expert systems and neural networks emerging as the most influential tools in enhancing strategic decision-making. Furthermore, there is a significant positive relationship between the dimensions of AI-driven business analytics and strategic decision-making, with a statistically significant effect at the 0.05 level. The study highlights the need for further development of digital competencies and adoption of AI tools to maximize their potential in educational contexts